Recovery of Polyhydroxyalkanoates From Single and Mixed Microbial Cultures: A Review - Pagliano, Giorgia; Galletti, Paola; Samorì, Chiara; Zaghini, Agnese; Torri, Cristian (Frontiers in Bioengineering and Biotechnology, 2021)
An overview of the main polyhydroxyalkanoates (PHA) recovery methods is here reported, by considering the kind of PHA-producing bacteria (single bacterial strains or mixed microbial cultures) and the chemico-physical characteristics of the extracted polymer (molecular weight and polydispersity index). Several recovery approaches are presented and categorized in two main strategies: PHA recovery with solvents (halogenated solvents, alkanes, alcohols, esters, carbonates and ketones) and PHA recovery by cellular lysis (with oxidants, acid and alkaline compounds, surfactants and enzymes). Comparative evaluations based on the recovery, purity and molecular weight of the recovered polymers as well as on the potential sustainability of the different approaches are here presented.